The impact of work–leisure facilitation on employees’ turnover intentions: the perspective of positive emotions - Wang, Feng; Zhang, Zihui; Shi, Wendian (Chinese management studies, 2024)
Purpose Work and leisure, as important activity domains, play important roles in the lives of individuals. However, most previous studies focused on only the interference and negative effects of work on leisure, with little focus on the facilitation of work and the positive effects of work on leisure. In view of the shortcomings of previous studies, this study focuses on the facilitation effect of work on leisure and its impact on individual psychology. This study aims to explore the relationship between work–leisure facilitation (WLF) and turnover intention and the role of positive emotions and perceived supervisor support in this relationship. Design/methodology/approach In this study, the method of multipoint data collection was adopted to measure the subjects; 180 employees were sampled for 5 consecutive working days, and a multilevel structural equation model was established for analysis. Findings The results show that WLF is negatively related to turnover intention, and positive emotions play a mediating role in this relationship. Perceived supervisor support significantly positively moderates not only the relationship between WLF and positive emotions but also the indirect effect of WLF on turnover intention through positive emotions. Originality/value Based on affective events theory, this study explored the relationship between WLF and turnover intention and its mechanism by using the daily diary sampling method for the first time, to the best of the authors’ knowledge. The results not only deepen the understanding of affective events theory but also provide management suggestions for reducing employees’ turnover intentions.